Incidence of Natural Conception in Fertility Couples Delayed Treatment in the COVID-19 Shutdown in Australia - Elizabeth Cutting; Emma Ebinger; Sascha Edelstein; Ben W. Mol (Fertility & Reproduction)
Background: In vitro fertilization (IVF) is the most widely applied fertility treatment. While the indication for IVF is not disputed in couples where natural conception chances are close to zero (blocked fallopian tubes or severe male infertility), it is less clear when IVF should be started in other couples. Natural conception occurs frequently and has been reported in patients pre- and post-IVF treatment. The outbreak of COVID-19 in the early months of 2020, resulted in Australian fertility clinics stopping treatment. This enabled the opportunity for fertility patients to try and conceive naturally. Methods: We studied couples who were scheduled to start IVF in March 2020 but who faced delayed treatment due to COVID-19 shutdowns. Outcomes were recorded as couples returned for treatment or were contacted via phone and asked why they did not return. We collected baseline characteristics including maternal age, day of next Day 1, and type of infertility, as well as the pregnancy outcome or reason for not returning. Results: We studied 533 couples who were delayed IVF treatment for a total of 1,204 observation months. From the initial cohort of 533 couples delayed treatment, 16 couples achieved pregnancy (3%) with 12 resulting in live birth (2.3%). When analyzed by indication, patients with ovulatory disorders (4 of 55 [7.2%]) or reduced ovarian reserve (7 of 141 [5%]) proved to have higher rates of natural conception compared to other diagnostic categories. There were 39 couples who did not return to treatment and did not achieve natural conception. Conclusion: There is a significant emotional toll that patients experience when undergoing fertility treatment. Natural conception is evident within cohorts scheduled for IVF treatment, and this study indicates that the chance per cycle of live birth in couples waiting to undergo medically assisted reproduction during the COVID pandemic was 2.3%.